Alterações agudas no metabolismo energético de ratos submetidos ao exercício resistido em escada - Silvestre, João Guilherme de Oliveira (Universidade Federal de São Carlos, 2012)
Previous animal s research has shown that many protocols with aimed to mimic human exercise has been used. The endurance protocols are studied very often however, some difficulties are encountered to produce resistance exercise protocols. Some animal models of resistance training have been used, as jumping exercise. Among these, stands out the rat model performed on ladder with healthy and unhealthy animals. However, the energy system and acute physiological responses associated with this protocol have not been determined. Thus, the aim of the present study was to evaluate the acute metabolic characteristics and the acute effects on indirect biomarkers of muscular microtrauma of acute resistance exercise performed on ladder. Fifty males Wistar rats were randomly divided into two groups: Exercise (E) and Control (C). The animals of E group climbed a vertical ladder with weights attached to their tails. The session was performed once with 4 9 climbs. The lactate concentration increased at the beginning of training and there was a tendency to stabilize the blood lactate during the exercise session. Serum corticosterone found in E group was significantly higher (59%; p<0.05) when compared to C group. There was no difference between free fatty acids (24% p=0.109), in the liver (8%; p=0.575) and in the gastrocnemius fatty acids content (17%; p=0.219). The glycogen in liver (42%; p<0.05) and soleus (56%; p<0.05) were different between groups. Lactate Dehydrogenase (LDH) and Creatine Kinase (CK) activities were significantly higher (LDH 32%; CK 27%; p<0.05) in the E than in the C group. The results suggest that this protocol is a high intensity exercise able to induce an increase in the lactate concentration at the beginning of exercise. Moreover, there were increases in indirect markers of muscle microtrauma in rats after a single exhaustive session. However, the lactate concentration was low, suggesting that the aerobic metabolism is an important factor during the intervals between the series of climbing.
Keywords: Fisiologia; Exercício Resistido; Metabolismo Energético; LDH; CK; Corticosterona; Lactato; Glicogênio; Ácidos graxos; Exercício agudo em escada; Resistance Exercise; Exercise Metabolism; LDH; CK; Corticosterone Hormone; Lactate; Glycogen; CIENCIAS BIOLOGICAS::FISIOLOGIA